Edith Stein and the Anselmian tradition - Grzesik, Tadeusz (Śląskie Studia Historyczno-Teologiczne, 2014)
Edith Stein is not usually associated with the thought of Anselm of Canterbury. However, when we read her “Endliches und Ewiges Sein”, we realize that she understood Anselm’s ratio of the Proslogion far better than Thomas Aquinas and effectively defended it against Aquinas’ criticism. Apart from their feeling for metaphysics, Anselm and Stein have another common feature: they both offer their testimony to the quaerere Deum aspect of religious life. The “intra in cubiculum mentis tuae” idea is an essential leitmotiv for them: they sought the solitude of the monastic cell in order to seek their Master without hindrance from the outside world and to contemplate the divinely instituted order of reality. In the present-day civilization of the West which does not “have God in its heart”, the example of St. Anselm “father of S cholasticism” and of St. Teresa Benedicta of the Cross – one of the patron saints of Europe, may serve to inspire those who seek a solution to the great spiritual void of Western society as well as save philosophy from disintegration.